Efeito da vacina Bm 86 no controle de Boophilus microplus (Canestrini,1887) e na imunidade contra a Trizteza Parasitária Bovina - Patricia Iria Anderegg (1999)
This study evaluated the association of the TickGard Plus vaccine and acaricide treatments on the control of Boophilus microplus and its effect on the bovine humoral immune response against babesiosis and anaplasmosis. Seventy two cross-bred Holstein x Tabapua cattle in a farm located in Carlos Chagas, Minas Gerais State, Brazil were divided into two groups. The vaccinated group had 72 animals, being 36 calves of 6 months old and 36 heifers of 17 months of age. The calves received 4 vaccinations of TickGard Plus and 3 acaricide treatments, while the heifers received 3 vaccinations and 2 acaricide treatments. A control group with 18 animals of each age received only acaricide treatments. at the same time of the vaccinated animals. Over a period of 8 months, serum samples were collected once a month and ticks were counted twice a month. Sera were analyzed by the indirect fluorescent antibody test for B. bovis; B. bigemina and A. marginale. The association was efficient in the control of the B. micmplus population for both age groups, however, during the period of higher natural challenge, heifers showed a significant lower tick infestation (4 ticks/anirhal) titan calves (52.7 ticks/animal). The vaccinated heifers showed a 62 to 95% decresse in the number of ault female ticks, and the calves showed a 18 to 93% decresse. With this association there was a reduction in the number of acaricide treatments. Regarding levels of antibodies, no significant differences were seen between vaccinated and control animals for both ages. These results suggest that the vaccine does not affect the humoral immune response to babesiosis and anaplasmosis.